A study on noise management and monitoring in public library / Norhidah Ahamad - Ahamad, Norhidah (Faculty of Architecture, Planning and Surveying, 2013)
A library is an organized collection of books, other printed materials, and in some cases special material such as manuscripts, films and other sources of information. People were encouraged to go to the library. In the library there are a lot of reading materials such as reference, books, magazines, newspapers and others. By reading, people can increase their knowledge. Those who are on the library will be spared from unhealthy symptoms such as loitering, smoking and others. Noise is unwanted sound. The results of national surveys of typical exposure to noise show that over 50% of the population are exposed to day-time noise levels that exceed the World Health Organisation (WHO) ratings for significant community annoyance. A satisfactory environment of sound quality therefore needs to be a major consideration when we create our built environment. This research was carried out to understand the noise management system in public library. The measurement of noise testing must be carried out to ensure the library follow the requirement of acceptable standard of sound in the library which is 30dB to 50dB.Besides that, this research also carried out to identify the sources of noise that lead to the noise in the library. From this research besides than the lack of design library, the human activities, noise from outside, renovation work and equipment in the building like air conditioning and escalator also give effect to the library performance